NASPGHAN Capsule Endoscopy Clinical Report. Issue 3 (March 2017) - Friedlander, Joel A.; Liu, Quin Y.; Sahn, Benjamin; Kooros, Koorosh; Walsh, Catharine M.; Kramer, Robert E.; Lightdale, Jenifer R.; Khlevner, Julie; McOmber, Mark; Kurowski, Jacob; Giefer, Matthew J.; Pall, Harpreet; et al.
Abstract : ABSTRACT: Wireless capsule endoscopy (CE) was introduced in 2000 as a less invasive method to visualize the distal small bowel in adults. Because this technology has advanced it has been adapted for use in pediatric gastroenterology. Several studies have described its clinical use, utility, and various training methods but pediatric literature regarding CE is limited. This clinical report developed by the Endoscopic and Procedures Committee of the North American Society of Pediatric Gastroenterology, Hepatology and Nutrition outlines the current literature, and describes the recommended current role, use, training, and future areas of research for CE in pediatrics.